Implementasi Model Pintar Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa - Muhammad Mahdianur; Dessy Dwitalia Sari (CV. ITTC INDONESIA, 2023)
The problem in this research is the low activity and learning outcomes of students at SDN Kelayan Selatan 3. The purpose of this research is to describe teacher activities, analyze student activities and student learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (CAR), with 4 meetings. The setting for this research was fourth semester students at SDN Kelayam Selatan 3 for the academic year 2022/2023. The results of the research that has been carried out show that teacher activity at meeting 1 reaches 75% of the